Complete blood counts with red blood cell determinants associate with reduced beta‐cell function in seroconverted Swedish TEDDY children. Issue 3 (3rd May 2021) - Salami, Falastin; N.Tamura, Roy; Elding Larsson, Helena; Lernmark, Åke; Törn, Carina
Abstract: Objectives: To investigate whether changes in complete blood count (CBC) in islet autoantibody positive children with increased genetic risk for type 1 diabetes are associated with oral glucose tolerance tests (OGTT) and HbA1c over time. Methods: The Environmental Determinants of Diabetes in the Young (TEDDY) study follows children with increased risk for type 1 diabetes in the United States, Germany, Sweden and Finland. In the current study, 89 Swedish TEDDY children (median age 8.8 years) positive for one or multiple islet autoantibodies were followed up to 5 (median 2.3) years for CBC, OGTT and HbA1c. A statistical mixed effect model was used to investigate the association between CBC and OGTT or HbA1c. Results: HbA1c over time increased by the number of autoantibodies ( p  < .001). Reduction in mean corpuscular haemoglobin (MCH) and mean cell volume (MCV) was both associated with an increase in HbA1c ( p  < .001). A reduction in red blood cell (RBC) counts ( p  = .003), haemoglobin ( p  = .002) and haematocrit ( p  = .006) levels was associated with increased fasting glucose. Increased red blood cells, haemoglobin, haematocrit and MCH but decreased levels of red blood cell distribution widths (RDW) were all associated with increased fasting insulin. Conclusions: The decrease in RBC indices with increasing HbA1c and the decrease in RBC and its parameters with increasing fasting glucose in seroconverted children may reflect an insidious deterioration in glucose metabolism associated with islet beta‐cell autoimmunity. Abstract : Islet beta cell autoantibody positive children with increased risk for developing type 1 diabetes have reduced red blood cell counts and parameters associated with impaired glucose metabolism.